Recent and ongoing selection in the human genome - Nielsen, Rasmus; Hellmann, Ines; Hubisz, Melissa; Bustamante, Carlos; Clark, Andrew G. (Nature reviews. Genetics, 2007)
Key Points Genes or genomic regions that are under selection will typically be functionally important and will often be disease associated. They are, therefore, of interest not only to evolutionary biologists, but also to researchers in the fields of functional genomics and disease genetics. Both negative selection acting against deleterious mutations and positive selection acting in favour of beneficial mutations is common in the human genome. Although most selection acting on segregating mutations in disease genes is negative selection — acting against deleterious, predominantly recessive mutations — some mutations in complex diseases might also have been affected by positive selection in the past or present. Several genome-wide scans for loci that are under selection have been carried out. These scans have provided a large amount of new information, but have also generated controversy as the concordance between results is not always high. The main reason for the lack of concordance is probably that different tests differ in their power to detect different forms of selection. However, statistical problems relating to assumptions about demography, recombination and ascertainment biases can also affect the results of some studies. Identifying regions of the human genome that have been subject to selection is key to understanding our evolution, and provides insights into the genetic basis of disease. However, important caveats require consideration when interpreting the results of attempts to identify selected regions. The recent availability of genome-scale genotyping data has led to the identification of regions of the human genome that seem to have been targeted by selection. These findings have increased our understanding of the evolutionary forces that affect the human genome, have augmented our knowledge of gene function and promise to increase our understanding of the genetic basis of disease. However, inferences of selection are challenged by several confounding factors, especially the complex demographic history of human populations, and concordance between studies is variable. Although such studies will always be associated with some uncertainty, steps can be taken to minimize the effects of confounding factors and improve our interpretation of their findings.